2018
DOI: 10.1001/jama.2018.14298
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Third-Trimester Tdap Immunization and Neonatal Pertussis Antibody Concentration

Abstract: Immunization with tetanus, diphtheria, and acellular pertussis (Tdap) vaccine is recommended in the United States during weeks 27 through 36 of pregnancy to prevent life-threatening infant pertussis. The optimal gestation for immunization to maximize concentrations of neonatal pertussis toxin antibodies is unknown. OBJECTIVE To determine pertussis toxin antibody concentrations in cord blood from neonates born to women immunized and unimmunized with Tdap vaccine in pregnancy and optimal gestational age for immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 34 publications
6
53
0
1
Order By: Relevance
“…No correlate of protection has been defined for pertussis ; however, high antibody levels are important . Several papers have used arbitrary thresholds when analysing pertussis antibody levels , and thus for our analysis we utilised the commonly used arbitrary threshold of ≥20 IU/ml for PTx, FHA and Prn antibody concentrations. A significantly higher percentage of infants from vaccinated pregnancies reached these antibody levels for tetanus and diphtheria, and the arbitrarily defined threshold for pertussis antibody in the first 7 weeks of life, compared to infants born from unvaccinated mothers.…”
Section: Discussionmentioning
confidence: 99%
“…No correlate of protection has been defined for pertussis ; however, high antibody levels are important . Several papers have used arbitrary thresholds when analysing pertussis antibody levels , and thus for our analysis we utilised the commonly used arbitrary threshold of ≥20 IU/ml for PTx, FHA and Prn antibody concentrations. A significantly higher percentage of infants from vaccinated pregnancies reached these antibody levels for tetanus and diphtheria, and the arbitrarily defined threshold for pertussis antibody in the first 7 weeks of life, compared to infants born from unvaccinated mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, three other studies found that vaccination during the early third trimester of pregnancy is associated with higher cord anti-B. pertussis-specific IgG levels than immunization during late third trimester (110)(111)(112). In addition, one study showed that anti-PT and anti-FHA IgG levels were higher in cord blood of mothers vaccinated between 13 and 25 weeks gestation compared to those immunized after 25 weeks gestation (113).…”
Section: Timingmentioning
confidence: 98%
“…Overall, studies of Tdap immunization of pregnant women showed that vaccination is well tolerated and immunogenic, resulting in transfer of high antibody levels to the fetus ( [45][46][47] and reviewed in [48][49][50]). Fewer studies have evaluated maternal Tdap vaccine effectiveness in preventing pertussis disease in infants, or the potential impact of the timing of vaccination, or underlying medical conditions such as human immunodeficiency virus (HIV) infection, on effectiveness.…”
Section: Introductionmentioning
confidence: 99%